PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PENGGUNA INDIHOME DI KARAWANG - Syahfitri, Mega Naliyah; Kusnanto, Danang (Buletin Studi Ekonomi; VOL.26.NO.2.AGUSTUS 2021DO - 10.24843/BSE.2021.v26.i02.p02, 2021)
This study aims to determine how the influence of product quality and service quality on IndiHome user decisions in Karawang. The population in this study were all IndiHome users in Karawang, with a total sample size of 100 respondents with the sampling method using snowball sampling. The data was collected by distributing questionnaires online via Google Form. This research was done by using verification and descripstion method were to know, to explain, to analyze and to do the hypothesis testing, and to make a conclusion and suggestion. The results of this study indicate that Product Quality has a positive and significant effect on IndiHome User Decisions in Karawang, and Service Quality has a positive and significant effect on IndiHome User Decisions in Karawang.